2022
DOI: 10.1177/13623613221074416
|View full text |Cite
|
Sign up to set email alerts
|

Individuals with autism show non-adaptive relative weighting of perceptual prior and sensory reliability

Abstract: Modulation in sensory-perceptual processing is a known characteristic of autism, although the underlying mechanism is debated. A prevailing account is formulated in Bayesian terms, where either a reduced prior or reduced noise in the measurement (sensory input) may account for the modulated perception as expressed by the posterior distribution. However, research has shown that individuals with autism use priors in some conditions, and to the same extent as neurotypicals, while other studies fail to show enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
3
5
0
Order By: Relevance
“…These findings suggest that autistic people can learn the statistics of the environment and implement them as prior knowledge. This is consistent with results from previous research that showed intact construction and utilization of prior in autism using simple visual and auditory stimuli such as visual judgment of size (Sapey-Triomphe et al, 2021;Binur et al, 2022) and weight , duration judgment (Karaminis F I G U R E 2 (a). Accuracy rates (mean ± SEM) for "switch stimuli" across groups in the two segments of the study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings suggest that autistic people can learn the statistics of the environment and implement them as prior knowledge. This is consistent with results from previous research that showed intact construction and utilization of prior in autism using simple visual and auditory stimuli such as visual judgment of size (Sapey-Triomphe et al, 2021;Binur et al, 2022) and weight , duration judgment (Karaminis F I G U R E 2 (a). Accuracy rates (mean ± SEM) for "switch stimuli" across groups in the two segments of the study.…”
Section: Discussionsupporting
confidence: 91%
“…These findings suggest that autistic people can learn the statistics of the environment and implement them as prior knowledge. This is consistent with results from previous research that showed intact construction and utilization of prior in autism using simple visual and auditory stimuli such as visual judgment of size (Sapey‐Triomphe et al, 2021; Binur et al, 2022) and weight (Hadad & Schwartz, 2019), duration judgment (Karaminis et al, 2016), and pitch discrimination (Lieder et al, 2019). The acquisition of priors in the present study with facial expressions extends previous research on social priors and show priors can be implicitly formed based on accumulated social information without explicit knowledge.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, on a probabilistic visual search task, autistic participants performed as well as comparison participants, except that reaction times were longer in the autism group when the target followed a distractor in a rare region of the search space (Allenmark et al, 2021). Binur et al (2022) found that autistic participants showed an equivalent width-height bias to comparison participants, but the blur effect on perceived width was attenuated in the autism group. Two trait-based studies also fell into this category.…”
Section: Resultsmentioning
confidence: 92%
“…This aids the rapid generation of largely accurate perceptual experiences (Press et al, 2020). To test this hypothesis, we refer to previous studies to reduce this relative reliability by blurring stimuli (Binur et al, 2022; Fourtassi & Frank, 2020; Rohlf et al, 2020). If the above framework holds, we expected facial expression clarity to modulate the effect of the scene on facial expression representation.…”
Section: Introductionmentioning
confidence: 99%